Cytotoxic effects of CeO2 NPs and β-Carotene and their ability to induce apoptosis in human breast normal and cancer cell lines - Al-Ali, Ali A.A.; Alsalami, Khalid A. S.; Athbi, Ahmed Muhssin (Iraqi Journal of Science, 2022)
Cerium Oxide Nanoparticles (CeO2 NPs) and β-carotene are natural-source products that have recently gained an increased interest as pharmaceutical additives because of their effectiveness in living systems, but the behavior of these substances varies according to factors and conditions. The above mentioned materials were evaluated in breast normal (HBL-100) and cancer cell lines (CAL-51 and MCF-7 ) by different techniques ; MTT assay for studying cytotoxic effects, morphological changes, sqPCR, including gene expression of caspases 8 and 9, and P53. All experiments were conducted on cell lines by the use of the materials alone as well as their combination. The results of the MTT assay showed that the two materials (CeO2 NPs and β-carotene) had a toxic effect on the cell lines, and the toxicity of the materials was concentration-dependent. The half maximal inhibitory concentration (IC50) values of CeO2 NPs and β-Carotene, as observed by the effects in all cell lines, have significant differences. Our findings showed that CeO2 NPs has a higher toxicity on the HBL-100 and MCF-7 cell lines compared with β-Carotene. The toxic effects of each material alone and combined together were reflected on cell morphology by the appearance of irreversible cytopathic changes in the treated cells. The two materials had the ability to cause cellular death and DNA damage, inducing the external pathway of apoptosis. A significant increase in the gene expression of caspase 8 appeared at P≤0.05. Collectively, the CeO2 NPs and β-Carotene have an inhibitory effect on both breast cancer and normal cell lines. We conclude the both materials have genotoxic effects on normal and cancer cell lines.